2003
DOI: 10.1172/jci200316804
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced growth of tumors in SPARC null mice is associated with changes in the ECM

Abstract: SPARC, a 32-kDa glycoprotein, participates in the regulation of morphogenesis and cellular differentiation through its modulation of cell-matrix interactions. Major functions defined for SPARC in vitro are de-adhesion and antiproliferation. In vivo, SPARC is restricted in its expression to remodeling tissues, including pathologies such as cancer. However, the function of endogenous SPARC in tumor growth and progression is not known. Here, we report that implanted tumors grew more rapidly in mice lacking SPARC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
114
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 40 publications
17
114
3
1
Order By: Relevance
“…Interestingly, the tumors that develop in SPARC null mice exhibit significant alterations in the production and organization of the extracellular matrix components, and these changes are believed to create a permissive environment for the accelerated tumor growth and invasion of cancer cells (Brekken et al, 2003). Our study supports the concept that SPARC influences tumor growth by regulating tumor stroma assembly.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, the tumors that develop in SPARC null mice exhibit significant alterations in the production and organization of the extracellular matrix components, and these changes are believed to create a permissive environment for the accelerated tumor growth and invasion of cancer cells (Brekken et al, 2003). Our study supports the concept that SPARC influences tumor growth by regulating tumor stroma assembly.…”
Section: Discussionsupporting
confidence: 78%
“…Murine pancreatic cancer cells injected orthotopically into SPARC-null mice grow larger and metastasize more frequently than those in wild-type mice, thus highlighting the importance of SPARC function and ECM composition in tumor progression (Arnold et al, 2008). The fact that the tumor cells, but not the infiltrating stroma cells, express and secrete SPARC in the aforementioned studies also supports the observation that the effect of SPARC on tumorigenesis is context-and cell-type dependent (Brekken et al, 2003;Puolakkainen et al, 2004).…”
Section: Discussionmentioning
confidence: 63%
“…23 Several lines of evidence suggest a tumor-suppressor role of SPARC in certain tumor types. [62][63][64][65] We have recently demonstrated that stromal SPARC patterns independently predict outcome in patients with pancreatic ductal adenocarcinoma. 66 SARP2 is an apoptosis-related gene that interacts the Wnt oncogenic signaling pathway.…”
Section: Discussionmentioning
confidence: 99%